(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The article analyzes the role of interreligious education in the context of social psychology. Since interfaith education has been an integral part of discussions about religious education since the mid- 1990s, the study of its impact on society is relevant in the modern world. The authors draw attention to the fact that before exploring the significance of psychological theories of bias for interfaith education, it is necessary to consider and outline various ways to understand the fundamental concepts of attitudes, biases, and religious education. The study also examined issues of attitudes-biases-interfaith education and socio-psychological theories about religious prejudice. These theories are presented in the following relation: religious prejudice as a “categorization problem” (cognitive theories), religious prejudice as an identity problem (social identity theory), and religious prejudice as a socialization problem (social learning theory). The authors, reflecting on the emergence of prejudice in society, believe that racial, ethnic and gender prejudices are acquired at an early stage of human life. Religious prejudices, in turn, are acquired as a result of a “perfectly normal” socialization process, in which a person grows up in a culture with specific prejudices about religion. Key words: interfaith education, prejudices, social identity, socialization.